Spermatic cyst development of Dendrophyllia ramea from the Alboran Sea, Western Mediterranean - Covadonga Orejas; Silvia Antón-Sempere; Alexis Terrón-Singler; Amalia Grau (PANGAEA, 2023)
This data set contains information on spermatic cyst development in the coral Dendrophyllia ramea: spermatic cysts sizes and maturation stage are included. A total of three polyps have been analysed per each coral colony and a total of three coral colonies have been analysed for each sampling month: February 2018, May 2017, July 2018 and October 2017. Samples have been collected in the protected area of Punta La Mona (Granada, Alborán Sea, western Mediterranean) between 30 and 37 meters depth by scuba diving.
In: Orejas, C et al. (2023): Reproductive features and gametogenesis of Dendrophyllia ramea from the Alboran Sea, Western Mediterranean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.957212